PENYULUHAN BAHAYA DIARE PADA ANAK DI DESA SEKINCAU WILAYAH KERJA PUSKESMAS SEKINCAU LAMPUNG BARAT - Andoko Andoko; Eka Yudha Chrisanto; Rika Yulendasari; Samsul Mubarok (JURNAL KREATIVITAS PENGABDIAN KEPADA MASYARAKAT (PKM), 2018)
ABSTRACT Diarrheal is still the leading cause of death in the world, about 5-10 million deaths/year. Morbidity and mortality rate caused by diarrhea still high. World Health Organization estimates 4 billion cases worldwide and 2.2 million are dead, and most children are under 5 years old. The purpose of the activity is to increase people knowledge about diarrhea in children, and using public health of Sekincau. The education was done at Saturday, December 16, 2017. Methods using education among mothers about diarrhea in the work area public  health center Sekincau West Lampung Barat. There was significant influence on mother's knowledge before and after education. Provision of education to people Keywords: Diarrhea, Children, Knowledge.